Developing A Local-Based Theoretical Understanding Of Domestic Violence Against Wives - Endut, Noraida; Mohd Hashim, Intan Hashimah; Azmawati, Azman Azwan (Universiti Sains Malaysia, 2010)
By focusing on the youths of Malaysia, this research investigates how cultural norms contribute towards the acceptance of violent behaviour between spouses amongst the Malaysia population, assesses the influence of religious and cultural beliefs on such acceptance and examine* the relationship between youths' ideas about the position of men and women in society and their understanding about domestic violence against wives